European Small Business Finance Outlook: December 2013 - Helmut Kraemer-Eis; Frank Lang; Salome Gvetadze (European Investment Fund (EIF), 2013)
This European Small Business Finance Outlook (ESBFO) provides an overview of the main markets relevant to EIF (equity, guarantees/securitisation, microfinance). It is an update of the ESBFO June 2013. We start by discussing the general market environment, then look at the main aspects of equity finance and the guarantees/SME Securitisation (SMESec) market. Finally, before we conclude, we briefly highlight important aspects of microfinance in Europe.
Keywords: 330